Perlindungan Hukum Bagi Pekerja yang di-PHK dan Dirumahkan Akibat Pandemi Covid-19 - I Komang Wahyu Permana; I Nyoman Gede Sugiartha; Ni Komang Arini Styawati (Warmadewa Press, 2022)
Due to the pandemic, many workers have been laid off or laid off. The problem that arises is how is the legal protection for workers who have been laid off due to the Covid-19 pandemic? And how is the legal protection for workers who have been laid off due to the Covid-19 pandemic? Normative legal research with a statutory approach was chosen to conduct this research. After conducting the research, it was found that legal protection for workers who were laid off due to the Pandemic was contained in Articles 153 and 156 of the Job Creation Law. The legal protection provided is prevention, clarifying mechanisms and providing certainty of compensation to laid-off workers. Meanwhile, legal protection for laid-off workers is stated in the SE of the Ministry of Manpower No. SE-05/M/BW/1998 and SE Ministry of Manpower No. M/3/HK.04/III/2020.